2022
DOI: 10.1111/ffe.13796
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode I+II fracture parameters and cracking trajectory of heterogeneous multilayer pavement structure containing reflective crack

Abstract: Using aggregate generation and packing algorithm technique coupled with finite element method, a part of reconstructed asphalt pavement structure with five layers and containing a bottom-up crack was simulated. For more realistic modeling and more accurate analyzing the cracking behavior of pavement, a region surrounding the initial crack (and bottom-up crack) region and its neighborhood was modeled as a heterogeneous two-phase (aggregate/mastic) mixture. The results of numerical analyses showed that a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…According to previous research works, every passage of a vehicle from the surface of cracked overlay with a topdown crack (initiated at the surface of road and normal to the road direction) can activated once dominantly mode I (or opening mode deformation) and twice dominantly shear (or in-plane mode II crack deformation) mechanisms. [83][84][85][86] Hence, the crack resistance performance and the overall service life of cracked overlays are influenced by the resistance of asphaltic mixtures against these two fracture modes. Thus, to examine the HMA mixture's fracture resistance in real applications, suitable characteristics indexes should be known for mode I and mode II loading cases.…”
Section: Mode I and Mode Ii Fracture Test Configurationsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous research works, every passage of a vehicle from the surface of cracked overlay with a topdown crack (initiated at the surface of road and normal to the road direction) can activated once dominantly mode I (or opening mode deformation) and twice dominantly shear (or in-plane mode II crack deformation) mechanisms. [83][84][85][86] Hence, the crack resistance performance and the overall service life of cracked overlays are influenced by the resistance of asphaltic mixtures against these two fracture modes. Thus, to examine the HMA mixture's fracture resistance in real applications, suitable characteristics indexes should be known for mode I and mode II loading cases.…”
Section: Mode I and Mode Ii Fracture Test Configurationsmentioning
confidence: 99%
“…This shows the significant influence of temperature on the cracking resistance of the investigated HMA mixture because at low-temperature conditions, the bitumen of aged RAPed part losses to some extent its stiffness and load-carrying capacity due to aging. But such RAPed mixtures can still be used in practical applications since according to the previous analyses of Aliha and coworkers, [84][85][86] the maximum stress intensity factor applied from heavy vehicles and heavy traffic to a topdown crack is approximately 7-8 times smaller than the fracture toughness of such RAPed mixtures. Indeed, according to the mentioned works, [84][85][86] the maximum value of stress intensity factor induced by a 10 ton vehicle on a top-down crack is about 0.1 MPa.m 0.5 , that is, significantly less than the range of fracture toughness values obtained in this research for both control and RAPed mixtures at low-temperature condition.…”
Section: Technical Characteristics (Fracture Toughness) Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pirmohammad and Majid‐shokor 17 analyzed a four‐layer pavement with a top‐down crack to study the effects of the vertical and horizontal vehicle wheel loads on the SIF and T‐stress. Aliha et al 18 and Ziari et al 19 used the aggregate generation method and packing algorithm to construct a multi‐layer heterogeneous asphalt pavement, modeled part of it as a two‐phase (aggregate/mastic) mixture, and showed that the heterogeneous modeling and simulation had fracture parameters that differed in magnitude and sign.…”
Section: Introductionmentioning
confidence: 99%